Perlindungan Hukum Tehadap Korban Kekerasan Psikologis Yang Dilakukan Oleh Istri Dalam Lingkup Rumah Tangga - Windrawati I. Abuba; Fence M Wantu; Zamroni Abdussamad (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is made for; (1) to understand the factors that can underlie the occurrence of psychological violence perpetrated by wives in the household sphere and to find out (2) what forms of legal protection are provided for victims of psychological violence perpetrated by wives in the household sphere. The research used by the researchers namely using the type of empirical legal research. Through a statutory approach and a case approach that is actually based on the source of case analysis obtained through interviews, while the legal materials used are primary legal materials and secondary legal materials. Underlying the occurrence of psychological violence perpetrated by the wife within the scope of the household are internal factors as well as external factors. Internal factors consist of: Family factors that discriminate, in the form of physical humiliation and the victim's job so as to generate income that is only sufficient for the needs of the family but not with the wishes of the perpetrator, can encourage the perpetrator to commit the psychological violence. Whereas external factors consist of: Economic factors and social environment as for excessive acts of using social media. The form of legal protection for victims of psychological violence perpetrated by wives in the household sphere, namely the form of protection has been explained in Law Number 23 of 2004 concerning the Elimination of Domestic Violence, which has been explained in Article 7 regarding psychological violence which has been considered as According to research materials by the researchers, this article explains what is meant in Article 5 letter b, namely behavior that results in fear, loss of self-confidence, loss of ability to act, feeling of helplessness, and/or severe psychological suffering to a person.